Crescimento e conversão da energia solar em Phaseolus vulgaris L. em função da fonte de nitrogênio - CUESTA, RAFAEL REYES; LOPES, NEI FERNANDES; OLIVA, MARCO ANTONIO; FRANCO, AVILIO ANTONIO (Revista Ceres, 2015)
.